2008
DOI: 10.1097/shk.0b013e31806ec26
|View full text |Cite
|
Sign up to set email alerts
|

Treatment With H2s-Releasing Diclofenac Protects Mice Against Acute Pancreatitis-Associated Lung Injury

Abstract: Impaired lung function in severe acute pancreatitis is the primary cause of morbidity and mortality in this condition. Hydrogen sulfide (H(2)S) is a naturally occurring gas that has been shown to be a potent vasodilator. Diclofenac is a nonsteroidal anti-inflammatory drug and has been shown to have anti-inflammatory, analgesic, and antipyretic activity. ACS15 is an H(2)S-releasing derivative of diclofenac. Little is known about its effectiveness as an anti-inflammatory drug. In this report, we describe the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 22 publications
1
49
0
Order By: Relevance
“…For instance, recent studies demonstrated that different H 2 S donors inhibit leukocyte infiltration in carrageenan-injected air pouch or hindpaw (23,41), gastric injury induced by anti-inflammatory nonsteroidal anti-inflammatory drugs (NSAID; Ref. 42), colitis induced by trinitrobenzenesulfonic acid (43) and into lung during caerulein-induced pancreatitis and systemic inflammation induced by high doses of LPS (44,45). The explanation for these apparent anomalies may be severalfold.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, recent studies demonstrated that different H 2 S donors inhibit leukocyte infiltration in carrageenan-injected air pouch or hindpaw (23,41), gastric injury induced by anti-inflammatory nonsteroidal anti-inflammatory drugs (NSAID; Ref. 42), colitis induced by trinitrobenzenesulfonic acid (43) and into lung during caerulein-induced pancreatitis and systemic inflammation induced by high doses of LPS (44,45). The explanation for these apparent anomalies may be severalfold.…”
Section: Discussionmentioning
confidence: 99%
“…For example, S-diclofenac (ACS 15) is H 2 S-releasing diclofenac, which comprises an H 2 S-releasing dithiol-thione moiety attached by an ester linkage to diclofenac (a nonsteroidal anti-inflammatory drug-NSAID). The effect of treatment with the NSAID diclofenac and its H 2 S-releasing derivative ACS15 on cerulein-induced acute pancreatitis and the associated lung injury has been investigated (Bhatia et al 2008a). Although these two drugs do not have any significant effect on the local pancreatic injury, ACS15 affords significant protection against acute pancreatitis-associated lung injury (Bhatia et al 2008a).…”
Section: H 2 S Donorsmentioning
confidence: 99%
“…NaSH (14 µmol/kg, intraperitoneal) significantly improved lung function (peak expiratory flow, peak inspiratory flow, intrapressure and maximum rising slope of intrapressure) and inhibited iNOS activation in the lung [64] Male C57B1/6 mice and male Wistar rats: Acute inflammation of the knee induced by kaolin-carrageenan S decreased synovial blood flow but had no effect on joint pain [69] Female C57BL/6 mice: Acute lung injury; B + S injury GYY4137 also decreased LPS-induced hypotension [32] In vitro cellular study using murine RAW264.7 macrophages significantly decreased reduced lung inflammation to a significantly greater extent than diclofenac alone; however, ACS15 was ineffective against pancreatic injury (i.e., acinar cell death, pancreatic neutrophil accumulation or plasma amylase) [129] Rats: OA-induced acute -independent oxidative burst [132] In vitro cellular study formyl-methionyl-leucylphenylalanine-and zymosan-activated serum stimulated polymorphonuclear cells …”
Section: S-mediated Inhibition Of Inosmentioning
confidence: 99%